The Feminist Voice in Chopin’s “The Awakening” & Atwood’s “The Edible Woman” - Hussein, Ahmed (Technium Social Sciences Journal, 2020)
This research paper intends to study Kate Chopin’s The Awakening and Margret Atwood’s The Edible Woman. These two novels demonstrate women’s defiance to the society and their struggle to obtain the freedom they desire. Both works strive to depict the female plight towards the quest of independence and fair share in a society ruled and dictated by patriarchy. The paper highlights how the notion of feminism is similar or otherwise different as presented in both works. The paper attempts to demonstrate that the structure and the elements of both works stress and affirm the feminist voice each work strives to make it heard in a world generally suffocating these voices.